Pengaruh Modal Terhadap Peningkatan Produksi Cengkeh Di Kelurahan Sawidago Kecamatan Pamona Utara - Abdi Sakti Walenta; Yuyun Alfasius Tobondo; Fredrik Bastian Kawani; Wildawati Dera (Fakultas Ekonomi Universitas Kristen Tentena, 2023)
This research aimed to analyzed the influence of land extensive, financial capital, employee toward the clove production outcome. The location of the research in Sawidago, North Pamona Sub District. The method is used in this research by surveyed 45 farmers respondent. Samples are randomly taken from the research location. Data is analyzed by using a simple and doubled regression analysis and then by F test.The result of the reseach show that land extensive variable, financial capital, employee have a significance influence toward the clove production outcome. R2 value in the amount of 0,960 means that 96% clove production outcome variable can explained by land extensive variable, financial capital and employee. While the balance that is 4% explained by other reason except financial capital.